1998
DOI: 10.1076/apab.106.1.46.4392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Natural Postnatal Maturation and the Spermine-Induced Maturation of the Rat Intestine

Abstract: In the suckling rats, orally provided spermine induced structural and biochemical changes in the intestine, which are characteristics of the postnatal maturation. This induced maturation was compared to that occurring spontaneously. Eight mumol spermine were administered orally once a day, for one or three days, to suckling rats which were 11 days old at the beginning of the experiment. The animals were killed 0, 2, 4, 6, 8, 10 hours or 3 days after the first treatment. Control rats from the same litter were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…III), as well as the organ wet weight itself, decreased drastically after spermine ingestion. These decreases support a loss of cells in the intestinal lumen, a phenomenon already proven by histological observations [1][2][3].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…III), as well as the organ wet weight itself, decreased drastically after spermine ingestion. These decreases support a loss of cells in the intestinal lumen, a phenomenon already proven by histological observations [1][2][3].…”
Section: Discussionsupporting
confidence: 74%
“…We have previously shown that exogenous spermine can induce morphological and biochemical modifications in the small intestine of suckling rats [1][2][3]. One of the morphological changes observed is a decrease of the villous height, confirmed by a decrease of specific activities (SA) of disaccharidases as lactase and maltase.…”
Section: Introductionmentioning
confidence: 97%
“…In this organ two phases characterize the effect of spermine (Wery et al 1992(Wery et al , 1996aWery & Dandrifosse, 1993;Kaouass et al 1996;Peulen et al 1998b;Dandrifosse et al 1999;; desquamation of the intestinal epithelium is followed by a hormonal cascade.…”
Section: Information From Studies Performed Using Sucking Ratsmentioning
confidence: 99%
“…Bile salts would remain in the lumen of the bowel, speeding up the desquamation of the tips of the villi. Alternatively, spermine and aldehydes derived from polyamines by metabolization would act on the immune system or epithelial cells, where they would induce the secretion of various cytokines such as interleukins 1β and 6 and tumour necrosis factor α (Kaouass et al 1997b;Peulen et al 1998b). This type of secretion has been observed after spermine administration, and could cause, for example, the production of NO and the oedema noted at the tips of the villi (O Peulen and G Dandrifosse, unpublished results), a phenomenon eventually reinforced by an inhibition of ATPase activities by spermine.…”
Section: Information From Studies Performed Using Sucking Ratsmentioning
confidence: 99%
“…In the first experiment, the suckling rats were treated once a day for 4 d, starting at 10 d of age, with similar amounts of the different polyamines or ornithine (10 mol per rat), these quantities being close to those used in other studies (24,26,28,37). Under these conditions, the putrescine, spermidine, and spermine amounts ingested daily by the 14-d-old rats were respectively 2-, 6-, and 30-fold those ingested by 28-d-old rats fed on Ico.…”
Section: Resultsmentioning
confidence: 95%